Lung cancer among butchers and slaughterhouse workers. - Kristensen, Tage S.; Lynge, Elsebeth (Scandinavian Journal of Work, Environment & Health, 1993)
The following three questions are examined in this critical evaluation of the literature on lung cancer among butchers: (i) do butchers have an excess risk of lung cancer, (ii) if yes, is this excess possibly caused by exposures in the work environment, and (iii) if yes, what then are the possible etiologic exposures? It was concluded that butchers probably have an excess risk of lung cancer. This excess risk can be explained partly, but not entirely, by tobacco smoking. The following four possible etiologic exposures are introduced: human papilloma viruses, nitrite, incomplete combustion products, and fumes from meatpacking materials. Three of these possible explanatory factors (nitrite, combustion products and fumes from packing) are not, or only to a limited extent, substantiated by the empirical data. It was recommended that the hypothesis concerning human papilloma viruses and also the possible role of work stress be tested in future studies.